2019
DOI: 10.9734/jammr/2019/v30i930230
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Combined Methanolic Leaf Extracts of Vernonia amygdalina and Gongronema latifolium Enhanced Glut 2 Expression in the Pancreas and Downregulates Serum Caspase 3 Activity of Streptozotocin-Induced Diabetic Wistar Rats

Abstract: Aim: The study evaluated the effects of the combined extracts of Vernonia amygdalina (VA) and Gongronema latifolium (GL) on pancreatic GLUT 2 expression and caspase 3 activity in streptozotocin (STZ, 45 mg/Kg)-induced diabetic rats. Study Design: Fifteen Albino rats were used for the study and were placed in 3 groups of 5 rats each: A - normal control, B – Diabetic control and C – experimental group. Place and Duration of Study: The study was carried out in the department of Anatomy, University of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
1
1
Order By: Relevance
“…These workers reported reduction in sperm cell concentration, in contrast to Irais et al [53] who reported no reduction in sperm cell concentration following treatment with A. indica. Also, there was a decrease in sperm cell concentration of groups treated with G. latifolium (PGL LD and PGL HD ), which is in contrast with reports by Akpaso et al [23] of increases in sperm cell concentration in animals treated with G. latifolium. There was no significant reduction in sperm cell concentration and motility in the group treated with low dose of combined extract (PAIGL LD ) when compared with the NC group.…”
Section: Median Lethal Dose Of Azadirachta Indica and Gongronema Lati...contrasting
confidence: 99%
See 1 more Smart Citation
“…These workers reported reduction in sperm cell concentration, in contrast to Irais et al [53] who reported no reduction in sperm cell concentration following treatment with A. indica. Also, there was a decrease in sperm cell concentration of groups treated with G. latifolium (PGL LD and PGL HD ), which is in contrast with reports by Akpaso et al [23] of increases in sperm cell concentration in animals treated with G. latifolium. There was no significant reduction in sperm cell concentration and motility in the group treated with low dose of combined extract (PAIGL LD ) when compared with the NC group.…”
Section: Median Lethal Dose Of Azadirachta Indica and Gongronema Lati...contrasting
confidence: 99%
“…Phytochemical evaluation of the plant shows it to be rich in essential oils, saponins and pregnanes, alkaloids, tannins, phytates, flavoniods, and oligosaccharides [21,22]. Akpaso et al [23] reported that there were increases in sperm cell concentration in animals treated with G. latifolium. Dasofunjo et al [24] reported also that the plant extract can be used in the management of erectilerelated dysfunction since it enhances sexual health and libido in male Wistar rats.…”
Section: Introductionmentioning
confidence: 99%